Schizophrenia risk gene ZNF536 modulates retinoic acid response and neuronal gene networks in SH-SY5Y cells - Kurishev, Artemiy O.; Abashkin, Dmitrii A.; Karpov, Dmitry S.; Marilovtseva, Ekaterina V.; Chaika, Yulia A.; Semina, Ekaterina V.; Golimbet, Vera E. (Frontiers in Molecular Neuroscience, 2025)
ZNF536, a brain-specific transcriptional repressor, has recently emerged as a candidate risk gene for schizophrenia (SZ), yet its functional role in human neurodevelopment remains poorly understood. We used CRISPR/Cas9 genome editing to generate a dual-allelic ZNF536 knockout model in SH-SY5Y cells, combining a 103 kb deletion encompassing SZ-associated intronic regions with a disruption of zinc finger domains in exon 2. We performed transcriptome profiling of mutant cells undergoing all-trans retinoic acid (ATRA)-induced differentiation and analyzed neurite outgrowth phenotypes. Knockout cells exhibited impaired activation of retinoic acid receptor (RAR) target genes, reduced neurite outgrowth, and failure of neuronal maturation. Gene set enrichment analysis uncovered dysregulation of E2F4-mediated cell cycle pathways. The targeted intronic deletion altered the expression of multiple SZ-associated genes, supporting the functional importance of cis-regulatory elements within ZNF536. These findings identify ZNF536 as a critical regulator of RA-responsive gene networks and neuronal differentiation, modulating neurogenic commitment through coordinated control of transcriptional repression and cell proliferation, and offer new mechanistic insights into its contribution to schizophrenia pathogenesis.